OPERASI EKONOMI DIGITAL DAN FINANSIALISASI KAPITALISME NEOLIBERAL AMERIKA SERIKAT - M. Chairil Akbar Setiawan (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2021)
The development of the Digital Economy in the last decade has become increasingly prominent and significant. The dynamics and transactions of the Digital Economy span from the corporate to household levels, from local to global scales. The use of advanced information technology in the internet field paved the way for the Digital Economy, especially in the financial or financial realm. This reality is directly correlated with the current of financialization of contemporary capitalism which has strengthened as one of the main features of Neoliberal capitalism since the 1980s.This study seeks to analyze the operation of the Digital Economy in the financial sector such as Venture Capital or Financial Technology within the framework of Political-Economy, particularly through the study of International Political Economy. The author believes that the birth and development of the Digital Economy can be understood in two aspects, namely, first, it is directly correlated with the financialization of global capitalism, especially since the current of Neoliberalism emerged in the decade of the 80s. Financial liberalization and deregulation that started in the United States became the starting point for international economic financialization. Changes to the model of transactions and financial products are a direct derivation of financial deregulation initiated by developed countries and global capitalists.Second, technological development is a reflection of the historical development of capitalism. This means that technology in the Digital Economy has a social character and aims to optimize the accumulation of contemporary capitalism. Digital Economy Technology is not independent of social and economic-political formations or entirely as a result of the inherent creativity of the natural impetus of scientific progress.